2017
DOI: 10.4172/pharmaceutical-sciences.1000228
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role of Pharmacist in Pre-chemotherapy Counseling Among Breast Cancer Patients

Abstract: Dang, et al.: Role of Pharmacist in Counselling among Breast Cancer PatientsThe understanding of adult patients receiving cancer chemotherapy of their regimen is important for better control of chemotherapy-related side effects. Often, patients forget, misunderstand or unsatisfied with the information received. The purpose of this study is to investigate the effectiveness of pharmacist-led pre-chemotherapy counselling on the knowledge of chemotherapy treated breast cancer patients. It is a randomized and prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
3
0
2
Order By: Relevance
“…Moreover the mean age of study and control group were fifty three and with no statistical significant differences between both groups regarding sociodemographic characteristics. These results approximately agreement with Chan et al [16] that assess emerging role of pharmacist in prechemotherapy counseling-amongbreast-cancer-patients. His result showed that all sample was female although males were not excluded.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover the mean age of study and control group were fifty three and with no statistical significant differences between both groups regarding sociodemographic characteristics. These results approximately agreement with Chan et al [16] that assess emerging role of pharmacist in prechemotherapy counseling-amongbreast-cancer-patients. His result showed that all sample was female although males were not excluded.…”
Section: Resultssupporting
confidence: 91%
“…In line with the present results Waller et al [3] indicated that providing preparatory information can improve knowledge in cancer patients undergoing chemotherapy. Furthermore, Dang et al [19] recommended pre-chemotherapy counseling to improve patient knowledge and understanding of the chemotherapy regimen received.…”
Section: Resultsmentioning
confidence: 99%
“…These include detection and/or prevention of therapy‐related problems, extensive education and counselling about the efficient use of medications, awareness of side effects and implementation and monitoring of all the plans for optimal therapeutic outcomes (Han et al., 2016; Hughes, Wibowo, Sunderland, & Hoti, 2017). Moreover, pharmacist‐led pre‐chemotherapy counselling could improve patient knowledge and understanding of the chemotherapy regimen received (Dang, Amiruddin, Lai, Low, & Chan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dang et al has conducted a pre-chemotherapy counseling by pharmacist in breast cancer patients. 18 Hardly any studies demarcated the counseling into pharmacological and non-pharmacological elements.…”
Section: Discussionmentioning
confidence: 99%